SYMBOLIC UNITS IN ENGLISH DIGITAL TEXTS: THEIR LINGUISTIC FUNCTIONS IN SOCIAL MEDIA COMMUNICATION (KONFERENSIYA, 2025)
The rapid expansion of digital communication has transformed how English speakers construct meaning in online environments. This evolution has popularized the use of symbolic units such as emoji, GIFs, reaction icons, hashtags, and expressive typographic forms which now function as essential elements of discourse. Rather than serving as ornamental features, these symbolic units encode affective, interpersonal, and pragmatic meanings that are increasingly inseparable from the textual content with which they co-occur. This study investigates the linguistic functions of symbolic units within English social media posts, drawing from multimodal discourse analysis and pragmatic theory. Findings indicate that symbolic units perform a range of functions, including tone modulation, stance marking, identity construction, and discourse organization. In combination with verbal text, they enable users to convey complex meanings that would otherwise remain ambiguous or unexpressed. The study contributes to ongoing discussions about multimodality, digital literacy, and the semiotic landscape of online communication